Category Theory In Geography? - Arlinghaus, Sandra L.; Kerski, Joseph (Quaestiones Geographicae, 2015)
Is mathematical category theory a unifying tool for geography? Here we look at a few basic category theoretical ideas and interpret them in geographic example. We also offer links to indicate how category theory has been used as such in other disciplines. Finally, we announce the direction of our research program on this topic as a way to facilitate the learning, and maintenance of learning, of GIS software – and in the spirit of Quaestiones Geographicae, invite debate, comment, and contribution to this program in spatial mathematics.